Gender research in the CGIAR Research Program on Policies, Institutions, and Markets in 2018 and 2019 - Vos, Andrea; Pyburn, Rhiannon (International Food Policy Research Institute, 2021)
This report analyses PIM’s 391 peer-reviewed 2018 and 20191 publications. We highlight key gender findings and discuss the challenges faced by researchers in doing gender analysis, with a view to documenting lessons learned and improving practices. It is hoped that the gaps and strengths identified in this report will be useful inputs for future research under PIM and One CGIAR.